Histone deacetylase inhibitors - Marzena Baran; Paulina Anna Miziak; Katarzyna Bonio (Kazimierz Wielki University, 2020)
The human genome is contained in chromatin, which is a complex macromolecular complex. It is made of DNA, histones and non-histone proteins. The structure of chromatin and the process of its rearrangement regulate the process of transcription, and hence gene expression.  Deacetylase (HDAC) is a group of enzymes that catalyzes the cleavage of acetyl groups from lysine residues in histone and nonhistone proteins. This reaction is catalyzed by zinc or NAD + ions [3]. Histone deacetylases are present in the cytoplasm or nucleus of eukaryotes [4, 5]. These enzymes have been divided into 5 classes (I, IIa, IIb, III and IV) due to the similarity in structure and origin. Vorinostat is one of the most studied HDAC inhibitors. It belongs to the second generation polar-planar hydroxamic acid derivatives that inhibit class I and II histone deacetylases. Panobinostat and belinostat are HDAC inhibitors derived from hydroxamic acid that have also entered clinical trials. Valproic acid, from the group of aliphatic acids, belongs to inhibitors of class I and IIα deacetylases and is an established drug anticonvulsants. Histone deacetylase inhibitors may be useful in the treatment of neoplasms because they influence the action of factors related to cell proliferation, may cause cell cycle arrest, and coordinate the action of apoptotic factors and induce apoptosis. There are several deacetylase inhibitors available as drugs and are in different phases of clinical trials. They differ in potency and enzyme specificity. However, it is still unknown which deacetylases are essential for initiating and sustaining metabolic pathways leading to tumor development.